Mothman, the Silver Bridge Collapse, and the Folklorization and Commemoration of Actual Events - Daly, Jack (Journal of Scientific Exploration, 2023)
By examining the songs, media, and material culture associated with the legendary monster Mothman, this paper shows how folklore can become commodified and what issues may arise as a result. By using Paredes’ theory of “folklorization” and McDowell’s concept of “commemoration,” legend scholars can track historical developments across space and time to understand the metamorphoses a legend undergoes and why. Ultimately, this paper uses the term “narrative hijacking” to describe the process in which a historical event such as the Silver Bridge collapse of 1976 is overshadowed by its association with a legend, which in this case, is the story of the Mothman.